Rancang Bangun Aplikasi Resto Berbasis Mobile Menggunakan Metode Personal Extreme Programming - Hadad, Heksa Bustomi; Hapsari, Rinci Kembang; Hakim, Permana Faddyahsari (Institut Teknologi Adhi Tama Surabaya, 2025)
In the current era of globalization, technological developments are taking place very rapidly, including the development of information and communication technology; one of the steps in the development of information and communication technology is the development of telecommunications technology, especially smartphones. The development of smartphone technology has influenced various fields, including the culinary field. Kebon Kota Tropical Resto is a company in the culinary field. Currently, Kebon Kota Tropical Resto still uses a manual ordering method to order food and drinks, and it takes a long time to deliver consumer orders because of the long distance between kitchens, illegible handwritten orders, order slips, forgotten orders, and long queues. Therefore, an application is needed that makes it easier for customers to order food and drink menus. In developing this restaurant application, one of the agile development models has been used, namely the personal extreme programming model. In the personal extreme programming model, there are various stages: requirements, planning, iteration initialization, design, implementation, system testing, and retrospective. Based on the ISO 9126 evaluation with 50 respondents, the value of each criterion was obtained. Namely, the Usability value was 86.72%, the Functionality value was 86%, the Efficiency value was 86.53%, and the overall value of the application quality was 86.16%. Based on these values, the Kebon Kota Tropical Resto application is outstanding.